Corticosteroid in the treatment of cerebral malaria - T. H. Rampengan; S. Salendu Warouw; J. M. Wantanea; Muzief Munir (Indonesian Pediatric Society, 1984)
From January 1978 up to December 1980, twenty patients diagnosed with cerebral malaria were admitted at the Department of Child Health, Medical School, Sam Ratulangi University, General Hospital, Manado. They were treated with chloroquin (10 mg/kg body weight/day) intramuscularly, divided into two equal daily doses for consecutive 1-3 days, then continued by chloroquin orally for three more days. All patients also received intravenous fluid drips, symptomatic treatment, and cortisone acetate (15 mg/kg body weight/day) intramuscularly divided into three equal daily doses for three days. Four (20 %) of the cases proved fatal. The remaining 16 (80 %) recovered within 8.5 days on the average, and regained complete consciousness generally within 2% days. No after effects were reported.